'Picture me heart disease free': understanding African Americans' cardiovascular disease experiences through a culture-centered approach. Issue 3 (4th May 2021) - York, Felicia N.; Tang, Lu
ABSTRACT: African Americans have a disproportionately high risk of premature death caused by cardiovascular diseases (CVDs) and related risk factors such as hypertension, high cholesterol, diabetes, and obesity. Heeding the culture-centered approach to communication's (CCA) call for community-based health solutions for marginalized populations, in this study African Americans living with CVDs and associated risk factors describe their experiences with the disease using a photovoice approach. Participants demonstrate tremendous agency in their efforts to adopt a healthy lifestyle and manage their heart diseases. Structural factors such as socioeconomic status, insurance, discrimination, and knowledge enable and constrain their agency. Several cultural factors, such as food culture, reluctance to see doctors, consumerism, and religiosity, mediate the relationship between structure and agency. Public health professionals and researchers can capitalize on our findings in promoting cardiovascular health among the African American communities.